Recent Nanotechnological Trends in the Management of Microbial Keratitis - Shraddha Jaiswal; Prabhavati Shinde; Vidya Tale (Journal of Ophthalmic & Vision Research)
Microbial keratitis (MK) is a sight-threatening ocular disease that needs rapid diagnosis and treatment to prevent more serious outcomes. The broad-spectrum topical antimicrobial treatment is currently the main pharmacological approach for MK management, yet its efficacy is increasingly challenged by evolving antimicrobial resistance, including multidrug resistance. Also, the ocular surface presents numerous challenges for standard topical drug delivery. The failure and ineffectiveness of current therapies have necessitated the development of novel therapeutic strategies to manage MK. With advances in nanotechnology in the biomedical field, various nanomaterials can be employed to control MK. The primary determinants of nanoparticles’ vast range of applications are their size, surface properties, and chemical makeup, which also happen to be the same elements that give rise to their poisonous and dangerous effects. In this study, we provide a perspective on the contact lens-associated corneal illnesses such as MK and explore how nanotechnology might help address this significant clinical issue. In addition, safety and toxicological concerns about the increasingly widespread use of contact lenses are also discussed.